Applicable law to matrimonial property regime, with occasion of commentary of the Judgment of the Appeal Court of Madrid, 30th September 2019 - Rodríguez Rodrigo, Juliana (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
The Appeal Court of Madrid has resolved the brought sue due the inclusion of specific assets in the inventory. The couple has Dutch nationality and, in the first instance, the wife proved Netherlands law, without opposition from her husband. The husband appeals alleging the application of Spanish law in order to exclude certain assets from the inventory. The Spanish judge, within the framework of article 9.2 CC, considers the Netherland law is the applicable legislation.